PENGARUH PROFITABILITAS DAN LEVERAGE DENGAN MODERASI CSR TERHADAP NILAI PERUSAHAAN KOSMETIK YANG TERDAFTAR DI BEI - Dinda Bistari; Endah Supeni (Jurnal Ekonomi, Bisnis dan Social, 2023)
This purpose of this research to examine the effect of profitability and leverage with CSR moderation on company value cosmetics listed on the BEI from 2018-2022. This research is a quantitative study. The population of this study are all cosmetic companies that have published financial reports on the BEI from 2018- 2022. In this study has used a purposive sampling method, so that 30 samples were obtained in this study. The method used in this study is multiple linear regression analysis method with Moderated Regression Analysis (MRA). Multiple regression result with a significant level of 0.05 : (1) Profitability has a effect on firm value. (2) Leverage has a effect on firm value. (3) CSR as a moderating and strengthen the effect of profitability on firm value. (4) CSR as a moderating and weakens the relationship between leverage on firm value.